Research on pipeline-type power frequency electromagnetic heating system and multi-layer winding based power regulation method - Feng Zhou; Longyun Liu; Zixuan Wang; Xin Tong; Yanping Liu (Case Studies in Thermal Engineering)
Aiming at the issues of complexity, high investment costs, limited heating efficiency improvement, high failure rate, and poor reliability of traditional intermediate and high frequency electromagnetic heating systems, we propose a pipeline-type power-frequency electromagnetic coupling heating device. This device is designed based on transformer principles and utilizes Maxwell's equations and Fourier's heat conduction equation theory to achieve high efficiency and uniform heating. By performing three-dimensional transient field analysis of the heating device, parameters such as the voltage of the primary winding and the secondary winding (pipeline) are calculated to validate the feasibility of the heating scheme. To further enhance the economic efficiency of the heating device, the magnetic induction strength of the core with different hollow sizes is investigated. From this, the optimal hollow radius of the core structure was determined, achieving a saving ratio of approximately 36.52 %. Temperature field analysis of the heating device demonstrated that setting the fluid inside the pipeline to a certain water flow rate can achieve efficient heating of the fluid. Additionally, for applications requiring power regulation, a multi-layer winding-based power regulation method is proposed. Calculations show that this method achieves a heating efficiency exceeding 98 % under four different power settings. Compared to mid- and high-frequency electromagnetic coupling heating and electrode boiler heating methods, the heating efficiency increases by 1.39 % and 8 %, respectively. The proposed pipeline-style power-frequency electromagnetic coupling heating device does not require a boiler body, power electronic components, or even a high-power electrical transformer, thus significantly reducing costs compared to mid-frequency electromagnetic heating devices and electrode boilers, greatly enhancing economic efficiency. The study results suggest that energy output can be managed as needed, reducing the impact of loading and unloading on the local power grid and equipment, demonstrating strong practicality. This provides a new effective heating approach for industrial production of hot water and steam, centralized heating in urban and rural areas, and thermal power plants.